The Researcher’s Pedagogical Charisma During the Public Defense of Research Findings - Borozan, Maia; Munteanu, Olga (Didactica Danubiensis, 2025)
Objectives: This research aims to examine the dimensions of a researcher's pedagogical charisma as manifested during the public defense of research findings. The study focuses on how this competence supports persuasion within the academic community and contributes to generating a sustained, positive impression. Prior Work: The discussion builds on existing literature conceptualizing pedagogical charisma as a set of skills enabling researchers to engage, influence, and inspire audiences in academic settings, particularly during public research presentations. Approach: The analysis draws on diverse theoretical perspectives on scholarly charisma, including personal characteristics, behavioral patterns, relational dynamics, functional roles, constructivist interpretations, and transdisciplinary frameworks. These perspectives are explored across cognitive, emotional, social, and expressive dimensions. Results: Key characteristics identified include authentic enthusiasm, adaptability, communicative expressiveness, empathy, and openness. Core features such as self-confidence, the ability to leave a lasting impact, and sincerity are examined in relation to audience perception. Emotional intelligence is highlighted as enhancing scientific communication and fostering greater audience engagement. Implications: The study underscores the importance of pedagogical charisma in research dissemination and academic communication. A charismatic presence facilitates effective information delivery, stimulates curiosity, fosters connections between academia and the public, and strengthens scholarly credibility. Moreover, it encourages critical thinking and meaningful exchange of ideas. Research Value: This work advances the conceptual understanding of pedagogical charisma and highlights its value as a professional asset, particularly in public research defenses and academic leadership.